The Development and Validation of a Scale Assessing Individual Schemas Used in Classifying a Smoker: Implications for Research and Practice - Berg, Carla J. (Oxford University Press, 2011)
INTRODUCTION: Half of college students who have smoked in the past month do not consider themselves smokers. Understanding one’s schema of smokers is important, as it might relate to smoking behavior. Thus, we aimed to develop a scale assessing how young adults classify smokers and establish reliability and validity of the scale. METHODS: Of 24,055 students at six Southeast colleges recruited to complete an online survey, 4,840 (20.1%) responded, with complete smoking and scale development data from 3,863. RESULTS: The Classifying a Smoker Scale consisted of 10 items derived from prior research. Factor analysis extracted a single factor accounting for 40.00% of score variance (eigenvalue = 5.52). Higher scores (range 10–70) indicate stricter criteria in classifying a smoker. The scale yielded a Cronbach’s alpha of .91. Current smoking (past 30-day) prevalence was 22.8%. Higher Classifying a Smoker Scale scores (p = .001) were significant predictors of current smoking, controlling for sociodemographics. Higher scores were related to being nondaily versus daily smokers (p = .009), readiness to quit in the next month (p = .04), greater perceived smoking prevalence (p = .007), not identifying as smokers (p < .001), less perceived harm of smoking (p < .001), greater concern about smoking health risks (p = .01), and less favorable attitudes toward smoking restrictions (p < .001). Among current smokers, higher scores were related to greater smoking frequency (p = .02), not identifying as smokers (p < .001), and less perceived harm of smoking (p < .001), controlling for sociodemographics. CONCLUSION: This scale, demonstrating good psychometric properties, highlights potential intervention targets for prevention and cessation, as it relates to smoking, risk perception, and interest in quitting.